Open Science and Research Data Management at UiT The Arctic University of Norway - Høydalsvik, Stein; Conzett, Philipp (2018)
Presentation at the Open Science Toolbox Start-up Workshop, Trondheim, 26.10.18 ( https://www.ntnu.no/ub/prosjekter/ostoolbox. ), arranged by NTNU.